PERUBAHAN KEHIDUPAN SOSIAL DALAM NOVEL DAUN YANG JATUH TAK PERNAH MEMBENCI ANGIN KARYA TERE LIYE - Nurweni Saptawuryandari (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The purpose of this to reveal the changes in social life, changes in the indetity of lower class life discussed in the teenage novel "Daun yang Jatuh Tak Pernah Membenci Angin. The method used in this study is a qualitative description, which is carried out by describing in full the changes in social identity consisting of social changes in lower class life contained in the novel. Besides qualitative descriptive methods, juxtaposed discuss social sociology, which is discussed on social mobility. Social mobility is a movement a person does socially so that his life will be even better. Through the movement "at least" there is a change in life, more so, his life in society becomes good or mild. Data retrieval is done through the library, namely by referring to techniques and note the contents of the novel discussed the problem. From the research results obtained from the novel reveals the change in the character of Tania who started life from the lower classes succeeded in increasing life to a higher class because of perseverance and sincerity increased, also because of the concern of the surrounding community, namely the caring of Danar figure.